Digital Image Shaping of Micro-celebrity City: Brand Building and Communication of Chongqing City Image on the Platform of TikTok - Wang, Keqi (Transactions on Social Science, Education and Humanities Research, 2024)
This paper aims to discuss how the social media platform represented by TikTok influences and shapes the micro-celebrity city in the digital era. This paper takes Chongqing as the research object. Through in-depth analysis and interviews, it was found that Chongqing is very popular on TikTok because of its unique three-dimensional traffic, magical architecture, and food culture. These elements form a unique visual symbol of Chongqing through creative digital image expression and social interaction, attracting many tourists and deepening people’s impression and comprehension of the city. This study reveals the crucial role of digital images in shaping the image of contemporary cities and provides new perspectives and strategic suggestions for urban brand management and social media marketing. Through an in-depth discussion of content creation, communication mechanisms, and user interaction on platforms such as TikTok, this study provides valuable insights and references for city image communication and city brand building.